2010
DOI: 10.1371/journal.pone.0013032
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Patients with Bipolar Disorder: Association with Depressive Symptoms and Alcohol Use

Abstract: BackgroundCognitive dysfunction is clearly recognized in bipolar patients, but the degree of impairment varies due to methodological factors as well as heterogeneity in patient populations. The goal of this study was to evaluate cognitive functioning in bipolar patients and to assess its association with depressive symptoms. Post hoc the relationship with lifetime alcohol use disorder was explored.Methodology/Principal FindingsThe study included 110 bipolar patients and 75 healthy controls. Patients with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
3
32
0
1
Order By: Relevance
“…Indeed, verbal memory deficits of large effect size have been consistently reported in BD (Bora, Yücel, Pantelis, & Berk, 2011), in particular with regard to immediate and delayed recall (Bora et al, 2009; Martínez-Arán et al, 2004; Van Der Werf-Eldering et al, 2010; van Gorp et al, 1998). Another study showed that immediate recall was significantly impaired in BD patients with more than 3 manic episodes when compared to HC (Cao, Passos, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, verbal memory deficits of large effect size have been consistently reported in BD (Bora, Yücel, Pantelis, & Berk, 2011), in particular with regard to immediate and delayed recall (Bora et al, 2009; Martínez-Arán et al, 2004; Van Der Werf-Eldering et al, 2010; van Gorp et al, 1998). Another study showed that immediate recall was significantly impaired in BD patients with more than 3 manic episodes when compared to HC (Cao, Passos, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A history of substance use disorder has also been associated with reduced inhibition, poor visual memory and conceptual reasoning/set-shifting compared to patients with BD without past history of substance use (Houston et al, 2014; Marshall et al, 2012; Sanchez-Moreno et al, 2009; van Gorp, Altshuler, Theberge, Wilkins, & Dixon, 1998). Findings are however still controversial as at an appropriately powered study including BD patients with past and current lifetime use disorders found no link between cognitive impairment, more specifically in the memory domain, and AUD in BD patients (Van Der Werf-Eldering, Burger, Holthausen, Aleman, & Nolen, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a MADRS score ≥20 (marker of moderate to severe depression) were excluded from the correlational analyses. This is based on previous evidence suggesting that measures of cognitive functioning collected during the severe phase of depression are not reliable indicators of individuals' mental abilities [46]. Demographic and cognitive results were considered to be statistically significant at a Bonferroni-adjusted p-value <.05.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, patients with AD suffer from significant cognitive impairment, even after extended periods of abstinence (2935). Moreover, in both BD and AD, deficits in executive functioning are particularly predictive of poor prognosis and psychosocial disability (3644). It is therefore possible that people who suffer from both conditions may be at greater risk for developing debilitating cognitive impairment and a more severe course of illness (2527).…”
Section: Introductionmentioning
confidence: 99%